2005
DOI: 10.2174/1570161054368544
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative-Nitrosative Stress as a Contributing Factor to Cardiovascular Disease in Subjects with Diabetes

Abstract: In diabetes, clear evidence has emerged for the presence of oxidative-nitrosative stress, which may be a consequence of a glucose-mediated imbalance of systemic antioxidant buffering capacity, coupled with increased production of free radical species. Although multiple metabolic pathways have been identified, which may contribute to oxidative stress in diabetes, the principal pathogenetic pathways and their key down-stream targets remain to be established. Evidence links oxidative stress in particular, to elev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 198 publications
(256 reference statements)
0
8
0
Order By: Relevance
“…The mechanisms responsible for the effects of hyperglycemia and diabetes on myocardial function and on coronary macro- and micro-vasculature are the object of intensive investigation. Among several putative mechanisms, the role of the reactive oxygen (ROS) and reactive nitrogen species (RNS) has been studied in a number of experimental models of diabetes (Stevens, 2005). Oxidative stress associated with deficient antioxidant systems has been reported to play a critical role in subcellular remodeling, calcium handling, and subsequent diabetic cardiomyopathy (Haidara et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms responsible for the effects of hyperglycemia and diabetes on myocardial function and on coronary macro- and micro-vasculature are the object of intensive investigation. Among several putative mechanisms, the role of the reactive oxygen (ROS) and reactive nitrogen species (RNS) has been studied in a number of experimental models of diabetes (Stevens, 2005). Oxidative stress associated with deficient antioxidant systems has been reported to play a critical role in subcellular remodeling, calcium handling, and subsequent diabetic cardiomyopathy (Haidara et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…We have recently reported that diabetes exacerbates ischemic brain injury by augmenting ER stress and apoptosis associated with enhanced CHOP induction in rats (Srinivasan and Sharma, 2011). Diabetes has been further postulated to induce oxidative/nitrosative stress in brain and also implicated in various micro-and macrovascular complications (Ergul et al, 2009;Mastrocola et al, 2005;Stevens, 2005). In addition, hyperglycemia augments ischemic brain injury via inducing glutamate excitotoxicity and NO-mediated toxicity following I/R (Wei and Quast, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Besides the direct effects of impaired insulin pathways as well as hyperglycaemia on myocardial metabolism, other relevant mechanisms include enhanced oxidative stress (Ceriello, 2002; Stevens, 2005), low oxygen availability secondary to coronary endothelial/vascular damage (Rask-Madsen and King 2007) and increased susceptibility to ischemia (Rytter, 1985; Hink, 2001; Cai, 2002). Relevant contributing mechanisms involve the endocrine function of the adipose tissue and the inflammatory pathway (Berg, 2005).…”
Section: Introductionmentioning
confidence: 99%